Retrograde jejunojejunal intussusception in a pregnant female after laparoscopic Roux-en-Y gastric bypass. Issue 5 (14th May 2018) - Khan, Khuram; Saeed, Saqib; Persaud, Amrita; Sbeih, Mohammad; Gray, Sanjiv; Ahmed, Leaque
Abstract: Adult intussusception is a rare complication after laparoscopic Roux-En-Y gastric bypass (LRYGB) surgery. Incidence of intussusception is on the rise as the demand of bariatric surgeries is increased to treat morbid obesity. Among the bariatric surgeries, LRYGB gastric bypass results in significantly higher weight loss with thinning of the mesentery resulting in increased risk for intussusception. Majority of intussusception cases after gastric bypass have been reported in non-pregnant patients. We report a case of retrograde jejunojejunal intussusception in 6 weeks pregnant female following laparoscopic gastric bypass, which was diagnosed with abdominal magnetic resonance imaging and managed successfully with resection and revision of the anastomosis.